WOMAN POSITION IN IRON MAN MOVIES - ANINDITHA, ANNISA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Aninditha, Annisa. 2014. Woman Position in Iron Man movies. Study Program ofEnglish, Department of Language and Literature, Faculty of Cultural Studies,Universitas Brawijaya, Malang. Supervisor: Fariska Pujiyanti. Co Supervisor: NurulLaily Nadhifah. Keywords: Movie, Patriarchal, Iron Man. Movie is one of literary works and electronic media. Movie becomes the best strategy to communicate and deliver message about what happens in this world. The movie makers or directors can express critics, complains or opinions about something as an aspiration. Many movie genres appear to satisfy the audience, especially Action movies. Iron Man is one of action genres that focus on the male character physical appearance as main character, for example strong, charismatic, charming and powerful. Man as main character or hero can lead the plot of the movie, hence he always becomes primary view. In Iron Man movies there are extra characters as the assistants of the main character, they are women, the use of female characters as a show the stereotype about the use of woman as the second sex. This movies describe the condition where women are inferior and men are superior portray about the gender bias. This research used patriarchal and mise-en-scene approach as the groundingtheory to analyze the Iron Man movie sequel which is reflected the Tony Stark (Iron Man) as the main character and Pepper Potts, Natalie Rush Man, Christine Everhart and Maya Hansen as the extra characters. The characters in Iron Man movie sequel and reference about patriarchal condition are used as supporting information for the analysis. The result of this study shows the weakness and inferiority of woman. Womanposition in sub-ordinate greatly describes Pepper Potts, Natalie Rush Man, Christine Everhart and Maya Hansen as extra character. It is suggested for further researcher use deconstruction approaches to analyze Tony Stark (Iron man) character, there are many interesting aspects related to the  characterization of the main character as hero which is different from the stereotypes of a hero which can be analyzed using deconstruction theory.